New low-cost biofilters for SARS-CoV-2 using Hymenachne grumosa as a precursor. (10th January 2022) - Demarco, Carolina Faccio; Afonso, Thays França; Schoeler, Guilherme Pereira; Barboza, Victor dos Santos; Rocha, Liziane dos Santos; Pieniz, Simone; Giongo, Janice Luehring; Vaucher, Rodrigo de Almeida; Igansi, Andrei Vallerão; Cadaval, Tito Roberto Sant'Anna; Andreazza, Robson
Abstract: The ongoing global spread of COVID-19 (SARS-CoV-2 2019 disease) is causing an unprecedented repercussion on human health and the economy. Despite the primary mode of transmission being through air droplets and contact, the transmission via wastewater is a critical concern. There is a lack of techniques able to provide complete disinfection, along with the uncertainty related to the behavior of SARS-CoV-2 in the natural environment and risks of contamination. This fact makes urgent the research towards new alternatives for virus removal from water and wastewater. Thus, this research aimed to characterize new lost-cost adsorbents for SARS-CoV-2 using Hymenachne grumosa as a precursor and verify its potential for removing SARS-CoV-2 from the solution. The aquatic macrophyte H. grumosa had in natura and activated carbon produced with H. grumosa and zinc chloride (ZnCl2, 1:1) impregnation and carbonization (700 °C, 1 h) were incubated for 24 h with inactivated SARS-CoV-2 viral suspension, and then the ribonucleic acid (RNA) was extracted and viral load quantified through reverse transcription-quantitative polymerase chain reaction (RT-qPCR) technique. The results demonstrated the great adsorption potential, achieving removal of 98.44% by H. grumosa "in natura", and 99.61% by H. grumosa with carbon activation, being similar to commercial activated carbon (99.67%). Thus, this study highlights the possibility of low-cost biofilters to be used for SARS-CoV-2 removal, as an excellent alternative for wastewater treatment or watercourses decontamination. Graphical abstract: Image 1